MENEBAR BENIH KEBENCIAN MELALUI VISUALISASI ‘BANCI’ KARTUN BENNY DAN MICE - Aniendya Christianna (Universitas Airlangga, 2016)
Cartoon with its concise, simple and attractive characteristic allows the reader to digest the ideas of the cartoonist. As one of the products of mass media, a cartoon is never neutral and value-free, it oftenly carries an ideology. Culture and the domination of an ideology contribute to the production process of the symbols that are articulated in a cartoon. This qualitative research used a methodology of critical study based on image-based research, which reveals the visual image as a research foundation. In the process of interpretation, the researchers are conducting a dialect with the text as an object. Then analyze it so that it becomes cohesive. After that, it could obtaine a relative reality. Benny and Mice cartoon implicitly states that heterosexuals are the 'normal' sex relationships. Beyond that, is a deviation. Deserves to be blamed, humiliated even ridiculed. Benny and Mice cartoon show that transsexual / transvestite / transgender as a source of fear. The package of it pictorial and verbal language wrapped in hyperbole and joke, and becomes the 'seeds' of homophobia amid the hegemony of heterosexual community.